IMPLEMENTATION OF THINK-PAIR-SHARE MODEL TO INCREASE THE SIXTH-GRADE STUDENTS’ LEARNING ACTIVITIES AND OUTCOMES AT SD NEGERI 4 PANARUNG - Theo Jhoni Hartanto; Pri Ariadi Cahya Dinata; Arini Arta Naibaho; Risnameli Risnameli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The lack of students’ learning activities and outcomes in class VI-B at SDN 4 Panarung is based on the teacher-dominated learning and lecture method. To overcome the problem, the classroom action research through the Think-Pair-Share model was applied to the students. This paper reports the improvement of the student’s learning activities and outcomes on the theme of